Substitution of soyabean meal by faba bean improves body weight, sperm production and testosterone concentration in mature Queue Fine de l’Ouest rams - Ben Said, Samia; Gmati, Rima; Aroua, Mohamed; Lassoued, Narjess; Rekik, Mourad; Mahouachi, Mokhtar (Springer, 2023)
The current study aimed at investigating the effects of partial or total substitution of soybean meal with faba bean on reproductive parameters of Queue Fine de l’Ouest rams. Eighteen adult rams (49.8 ± 3.7 kg and 2.4 ± 1.5 years old) were divided into three homogenous groups. Rams received oat hay ad libitum and 3 types of concentrate (33 g/BW0.75) where soybean meal was the main protein source (SBM diet, n = 6), partially (50%, SBMFB diet, n = 6) or totally (100% FB diet, n = 6) substituted in nitrogen basis by local faba bean. The volume of ejaculate, sperm concentration and sperm mortality rate were measured weekly by collecting semen using an artificial vagina. Serial blood samples were collected 30 days and 120 days after the beginning of the experiment in order to assess plasma testosterone concentrations. The results showed that hay intake was affected (P < 0.05) by the nature of the nitrogen source incorporated (1032.3 ± 12.2; 1026.8 ± 56.6 and 972.8 ± 39.05 g DM/d for SBM, FB and SBMFB respectively. The average live weight of the rams increased from 49.8 ± 0.4 (week 1) to 57.3 ± 0.9 kg (week 17) without effect of the diet. A positive effect of faba bean incorporation in the concentrate was observed on ejaculate volume, concentration and spermatozoa production. All these parameters were significantly higher in SBMFB and FB groups than in SBM group (P < 0.05). The protein source did not affect the percentage of dead spermatozoa and the total abnormalities which were similar for the three diets (38.7; 35.8 and 38.1% for SBM; SBMFB and FB, respectively). The mean testosterone concentration was higher (P < 0.05) in rams fed with faba bean (1.7 ± 0.7 to 1.9 ± 0.7 ng/ml for the SBMFB and the FB groups respectively) than in rams fed SBM diet (1.06 ± 0.5 ng/ml). It was concluded that the substitution of soybean meal by faba bean improved the reproductive performance and did not affect sperm quality in Queue Fine de l’Ouest rams.